(untitled) (American Journal of Islam and Society, 2020)
Despite all the written works circulated or published so far, the effort to develop Islamic economics as a discipline does not seem to have brought about the expected results. This paper argues that it is the absence of a clear notion of what economics can be considered (and henceforth be given the prefix) Islamic that impedes the development of Islamic economics. To rectify the problem, this paper hence proposes three main conditions under which an economics can be considered Islamic. This paper further proposes that the scope of Islamic economics consists of four distinguished fields of work, and that the methods used in the development of Islamic economics vary depending on the end sought within each of these fields of work. This paper finally expands on three implications, which together give rise to a hope that to develop Islamic economics and its body of knowledge can be much less complicated than what Islamic economists have ever thought. This paper as a whole can be seen as a beginning statement toward a new, more comprehensive framework of Islamic economic analysis.